ANALISIS SWOT KINERJA KARYAWAN DAN MINAT NASABAH DALAM PENINGKATAN KUALITAS PEMBIAYAAN DI LEMBAGA KEUANGAN SYARIAH(STUDI KASUS DI (LKS) ASRI TULUNGAGUNG) - Mu'alifah; Riza Taufiqi Majid; Imam Thoha (Comprehensive Journal of Islamic Studies, 2023)
This research aims to determine the development of employee performance and customer interest in improving the quality of financing at the ASRI Tulungagung Sharia Financial Institution (LKS). The research method used is a quantitative descriptive method. The SWOT analysis used is the descriptive analysis method, SWOT Matrix and SWOT diagram analysis. Data collection techniques in this research are interviews, questionnaires and observation, documentation, literature. The results of this research show that the SWOT analysis based on the Internal-External Matrix (IE Matrix) of employee performance has a total IFAS score of 2.75 and a total EFAS score of 2.30. Meanwhile, the Cartesian diagram analysis of IFAS employee performance is 1.05 and the EFAS value is 1.70. The total score for internal factors of customer interest is 2.80 and the total score for external factors is 3.09. Meanwhile, Cartesian diagram analysis of IFAS employee performance is 1.05 and the EFAS value is 1.70. The total score for internal factors of customer interest is 2.80 and the total score for external factors is 3.09. Meanwhile, Cartesian diagram analysis of IFAS customer interest is 1.50 and EFAS is 1.21. This shows that employee performance has a high value of strengths and opportunities rather than weaknesses and threats and customer interest is very large in terms of strengths and opportunities so that it can minimize weaknesses. and threats that exist within the company so that it can be said that employee performance can improve the quality of financing at the ASRI Tulungagung Sharia Financial Institution.